Wpływ globalizacji na rozwój miast (Vlivy globalizace na rozvoj mést) - Milerski, Osvald (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In this paper there are described ways of global economics influences on big cities that proceed in highly liberalized but also unorganized marked environment. It draws our attention to the fact, that not all influences are desirable and unavoidable and reminds that there already exist verified instruments that can help us to reduce some undesirable effects of globalization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 56-66